The genomic basis of army ant chemosensory adaptations - McKenzie, Sean K. (2021)
The evolution of mass raiding has allowed army ants to become dominant arthropod predators in the tropics. Although a century of research has led to many discoveries about behavioural, morphological and physiological adaptations in army ants, almost nothing is known about the molecular basis of army ant biology. Here we report the genome of the iconic New World army ant Eciton burchellii, and show that it is unusu-ally compact, with a reduced gene complement relative to other ants. In contrast to this overall reduction, a particular gene subfamily (9-exon ORs) expressed predomi-nantly in female antennae is expanded. This subfamily has previously been linked to the recognition of hydrocarbons, key olfactory cues used in insect communication and prey discrimination. Confocal microscopy of the brain showed a correspond-ing expansion in a putative hydrocarbon response centre within the antennal lobe, while scanning electron microscopy of the antenna revealed a particularly high den-sity of hydrocarbon-sensitive sensory hairs. E. burchellii shares these features with its predatory and more cryptic relative, the clonal raider ant. By integrating genomic, transcriptomic and anatomical analyses in a comparative context, our work thus pro-vides evidence that army ants and their relatives possess a suite of modifications in the chemosensory system that may be involved in behavioural coordination and prey selection during social predation. It also lays the groundwork for future studies of army ant biology at the molecular level.